Sequences in the U5-gag-pol region influence early and late pathogenic effects of Friend and Moloney murine leukemia viruses. - Sitbon, M (1990)
Friend replication-competent murine leukemia virus (F-MuLV), clone 57, induces a severe early hemolytic anemia and a later erythroleukemia after inoculation of newborn IRW or ICFW mice, whereas Moloney MuLV (M-MuLV) induces only lymphoid leukemia. We have shown previously that the attenuated hemolytic and erythroleukemogenic abilities of an F-MuLV variant, clone B3, were due mostly to changes in the env gene and long terminal repeat, respectively. For the present study, we derived two constructs exchanging env fragments of F-MuLV 57 and M-MuLV and compared them with two constructs described by Chatis et al. (J. Virol. 52:248-254, 1984) exchanging the U3 region of the long terminal repeat of the same parental viruses. When comparing the hemolytic effect of these constructs with those of the parent, we found that the U5-gag-pol region of F-MuLV was required for development of severe early hemolytic anemia and that, unlike the env of F-MuLV B3, the env of M-MuLV was fully competent in inducing severe early hemolytic anemia when associated with the F-MuLV U5-gag-pol and U3 regions. As expected, induction of erythroleukemia depended on the presence of the F-MuLV U3 region; however, the presence of both the U3 and U5-gag-pol regions of F-MuLV appeared to be synergistic and was associated with a more rapid appearance of erythroleukemia.